2013
DOI: 10.1523/jneurosci.3146-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Brain Networks in the Awake, Truly Resting Marmoset Monkey

Abstract: Resting-state functional MRI is a powerful tool that is increasingly used as a noninvasive method for investigating whole-brain circuitry and holds great potential as a possible diagnostic for disease. Despite this potential, few resting-state studies have used animal models (of which nonhuman primates represent our best opportunity of understanding complex human neuropsychiatric disease), and no work has characterized networks in awake, truly resting animals. Here we present results from a small New World mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
154
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(187 citation statements)
references
References 71 publications
(16 reference statements)
28
154
0
Order By: Relevance
“…Research on rodent rs-fMRI repeatedly observed motor and somatosensory RSNs under anaesthesia (Hutchison et al, 2010, Lu et al, 2012, Grandjean et al, 2014a, Mechling et al, 2014, Nasrallah et al, 2014c comparable to those detected in awake rats (Liang et al, 2011(Liang et al, , 2012. Sensorimotor networks have been observed in monkeys and humans both under anaesthesia and at conscious rest (Peltier et al, 2005, Vincent et al, 2007, Martuzzi et al, 2010, van den Heuvel and Pol, 2010, Belcher et al, 2013.…”
Section: Discussionmentioning
confidence: 81%
“…Research on rodent rs-fMRI repeatedly observed motor and somatosensory RSNs under anaesthesia (Hutchison et al, 2010, Lu et al, 2012, Grandjean et al, 2014a, Mechling et al, 2014, Nasrallah et al, 2014c comparable to those detected in awake rats (Liang et al, 2011(Liang et al, , 2012. Sensorimotor networks have been observed in monkeys and humans both under anaesthesia and at conscious rest (Peltier et al, 2005, Vincent et al, 2007, Martuzzi et al, 2010, van den Heuvel and Pol, 2010, Belcher et al, 2013.…”
Section: Discussionmentioning
confidence: 81%
“…Such coactivations can also be observed with functional MRI (fMRI). In visual cortex, regions selective for either foveal or peripheral stimuli, show correlated blood-oxygen level-dependent (BOLD) activity in anesthetized (7) and resting (8) monkeys. In human subjects, BOLD activity in visual areas is organized into highly specific maps (9-11), the organization of which reflect anatomy (12) and the specificity of which is affected by blindness (13).…”
mentioning
confidence: 99%
“…Important higher order cognitive functions such as memory consolidation and selfreferential processes also involve RSNs (Albert et al, 2009;Van Den Heuvel and Pol, 2010;Wicker et al, 2003), which allow individuals to review past experiences and plan future actions. RSNs similar or homologous to those of humans have been identified in monkeys (Belcher et al, 2013; and rodents (Lu et al, 2012;Sforazzini et al, 2014;Zhao et al, 2008). These findings suggest RSNs is a primitive feature of the mammalian brain .…”
Section: Introductionmentioning
confidence: 60%